High-purity high-alpha-phase nano-alumina, and preparation method and application thereof

CN122877778APending Publication Date: 2026-10-09ANHUI ESTONE MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611020335.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

若通过加入矿化剂等来降低晶型转化温度,虽可在一定程度上缓解颗粒烧结,但会引入外来杂质,导致产品纯度降低,甚至带来环保方面问题

Benefits of technology

[0032](1) 本发明中的原料氧化铝经过至少两次水热处理,第一次水热反应清除大部分可溶性离子杂质,并通过初步的相变将杂质从主体铝结构中“排挤”出来,实现初步纯化;后续水热反应通过深度再结晶和奥斯特瓦尔德熟化,实现固相内部的“新陈代谢”,将第一步残留的、包裹的或共沉淀的杂质深度清除,最终得到结晶更完整、化学成分更纯净的氧化铝。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122877778A_ABST
    Figure CN122877778A_ABST
Patent Text Reader

Abstract

The application discloses high-purity high-alpha-phase nano alumina and a preparation method and application thereof, and relates to the technical field of inorganic powder. The preparation method comprises the following steps: (1) performing at least two hydrothermal reactions on alumina to obtain a reaction product; (2) performing first calcination on the reaction product to obtain a calcination product; and (3) mixing the calcination product with a carbon source additive, performing second calcination under vacuum or in an inert atmosphere, introducing air after reaching the calcination temperature, and performing heat preservation to obtain high-purity high-alpha-phase nano alumina. The industrial alumina is used as a raw material, the prepared nano alumina has the characteristics of spherical particle morphology, high purity, high alpha-phase content, narrow particle size distribution and the like, and the production cost is low, the preparation method is simple, and the preparation method is environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of inorganic powder technology, specifically to a high-purity, high-α-phase nano-alumina, its preparation method, and its application. Background Technology

[0002] Alumina (Al₂O₃) has various crystal forms, among which α-alumina is the thermodynamically stable phase, possessing excellent wear resistance, high hardness, strong corrosion resistance, and superior thermal stability. It has wide applications in ceramics, battery separators, composite coatings, composite materials, new medical materials, semiconductor and electronic engineering materials, catalysts and their supports, and polishing materials. As the application fields of alumina continue to expand, the requirements for its powder performance are increasing, with trends towards nano-sizing, high purity, sphericity, and high α-phase conversion rate. However, simultaneously achieving these four performance indicators remains a recognized technical challenge in this field.

[0003] To obtain nanoscale alumina, existing technologies mainly employ the following two approaches:

[0004] The first approach is the gas-phase method, which uses organic aluminum salts, inorganic aluminum salts, or aluminum powder as raw materials to prepare nano-alumina through combustion hydrolysis, flame pyrolysis, laser evaporation, etc., under high-temperature conditions. However, the products obtained by this method still contain multiple transition phases such as γ, δ, and θ, with a low α phase content, and the particle morphology is mostly worm-like with poor sphericity. Therefore, alumina particles prepared by the gas-phase method using aluminum chloride as raw material are usually amorphous or transition alumina particles, with a crystalline form of any one of γ, δ, or θ or a mixture thereof, rather than a stable α phase. Patent CN119911947A discloses a vacancy-isolated preparation method for monodisperse nano-α-alumina. Although it adopts the "vacancy isolation" technical route, it also clearly points out the technical contradiction of "grain merging and growing into a worm-like shape during the transformation of the unstable phase to the α phase".

[0005] The second approach is the sol-gel method, which uses aluminum sol as a precursor. It involves introducing α-alumina seeds to induce crystal transformation, followed by drying and calcination to prepare nano-alumina. This method lowers the crystal transformation temperature to some extent, but its ability to control the product morphology is limited, and worm-like structures are still prevalent. Patent CN115818690A discloses a method for preparing electronic-grade near-spherical α-Al₂O₃ powder. Using industrial alumina, boehmite, or angular α-Al₂O₃ as raw materials, and ammonium fluoride, magnesium oxide, and boric acid as composite mineralizers, the method involves mineralizer pretreatment, phase transformation processes, purification, and depolymerization to obtain near-spherical α-Al₂O₃ powder. While the product exhibits high sphericity and high α-phase content, the introduction of mineralizers raises issues regarding product purity and environmental treatment.

[0006] Existing methods struggle to simultaneously achieve nano-sized, high-purity, spherical, and high-α-phase alumina powders. Those skilled in the art point out that the fundamental reason lies in the interrelationships among these performance indicators. For instance, since the phase transformation temperature of α-alumina is typically above 1000℃, when unstable nano-alumina transforms into nano-α-alumina above 1000℃, sintering and adhesion occur between nanoparticles driven by surface energy. The particles rapidly merge and grow, forming a worm-like shape, significantly reducing sphericity and increasing particle size. While adding mineralizers to lower the crystal transformation temperature can alleviate particle sintering to some extent, it introduces foreign impurities, leading to reduced product purity and even environmental problems.

[0007] In addition, existing technologies have to use high-purity and high-cost precursor raw materials such as aluminum alkoxides in order to obtain products with high purity, which brings significant cost disadvantages to large-scale industrial production. Summary of the Invention

[0008] To address the shortcomings of existing technologies, this invention provides a method for preparing nano-alumina. The obtained nano-alumina simultaneously possesses characteristics such as spherical particle morphology, high purity, high α phase, and narrow particle size distribution. Furthermore, it features low production cost, simple preparation process, and environmental friendliness.

[0009] The technical problem to be solved by this invention is achieved by the following technical solution:

[0010] The first objective of this invention is to provide a method for preparing high-purity, high-α-phase nano-alumina, comprising the following steps:

[0011] (1) Alumina is subjected to at least two hydrothermal reactions to obtain the reaction product;

[0012] (2) The reaction product is calcined for the first time to obtain the calcined product;

[0013] (3) The calcined product is mixed with carbon source additives and calcined a second time under vacuum or inert atmosphere. After reaching the calcination temperature, air is introduced and the temperature is maintained to obtain high-purity high α phase nano alumina.

[0014] This invention does not particularly limit the crystal form of the alumina raw material, and any crystal form known in the art can be used, including but not limited to one or more of α-alumina, γ-alumina, θ-alumina, δ-alumina, and amorphous alumina. In a specific embodiment of this invention, an alumina raw material with a γ-alumina content of 96% is used, with the balance being other crystalline phases or amorphous phases, and an average particle size of 5-10 μm. However, this invention is not limited to this.

[0015] In this invention, the at least two hydrothermal reactions include a first hydrothermal reaction and at least one subsequent hydrothermal reaction; further, the at least two hydrothermal reactions can be two, three, four or more hydrothermal reactions. Preferably, the reaction temperature of the subsequent hydrothermal reaction is higher than that of the first hydrothermal reaction.

[0016] In a specific embodiment, the at least two hydrothermal reactions include the following steps: mixing alumina with water to form a slurry, heating the mixture to react, and washing the product with deionized water after the reaction is complete until the conductivity (EC) is <50 μS / cm, to obtain the first hydrothermal reaction product; mixing the first hydrothermal reaction product with water to form a slurry, heating the mixture to react, and washing the product with deionized water after the reaction is complete until EC is <50 μS / cm, to obtain the second subsequent hydrothermal reaction product; repeating this operation until the final reaction product is obtained.

[0017] Furthermore, the solid content of the slurry in the first hydrothermal reaction is 10-50%, the reaction temperature is 100-130℃, and the reaction time is 24-36 h; the solid content of the slurry in the subsequent hydrothermal reaction is 30-60%, the reaction temperature is 180-230℃, and the reaction time is 10-36 h.

[0018] Furthermore, the reaction product obtained in step (1) is dispersed to an average particle size of 0.1~0.4 μm. The purpose of dispersion is to break up the soft agglomerates formed by particle aggregation during hydrothermal process, reduce the particle size range of the product, ensure uniform heating of the powder during the subsequent first calcination process, avoid incomplete calcination and excessive differences in the degree of crystal phase transformation caused by local particle accumulation, and provide a precursor with uniform particle size for the subsequent uniform coating of carbon additives and spheroidization by secondary calcination.

[0019] Furthermore, the first calcination is carried out in an air or oxygen atmosphere.

[0020] Furthermore, the calcination temperature for the first calcination is 1100~1300℃, and the holding time is 1~5 h.

[0021] Furthermore, after the first calcination, the calcined product is dispersed to an average particle size of 0.1~0.3 μm. The purpose of dispersion is to eliminate sintering necks formed by the particles after the first calcination, ensuring the uniformity of near-spherical particles during the second calcination. Dispersion is a common step in the art, and this embodiment of the invention does not impose a more specific limitation on it; exemplaryly, the dispersion method is air jet milling, but the invention is not limited thereto.

[0022] In this invention, the role of the carbon source additive is to generate activated carbon through decomposition during high-temperature calcination, and the impurity content is <0.01%.

[0023] Furthermore, the carbon source auxiliaries are organic carbon sources and / or carbon materials. Specifically, the organic carbon source is one or more of sugars, polyols, organic acids, and oxygen-containing polymers, including but not limited to glucose, fructose, sucrose, maltose, lactose, starch, cellulose, glycerol, and lignin; the carbon materials include but are not limited to one or more of graphite, carbon black, graphene, carbon nanotubes, amorphous carbon, fullerene, and diamond. Any similar materials that can achieve the purpose of this invention can be used as substitutes, and the substituted technical solutions still fall within the concept of this invention.

[0024] Further, the mass ratio of the calcined product to the carbon source additive is 10:(1~5). For example, it can be 10:1, 10:1.5, 10:2, 10:2.5, 10:3, 10:4, 10:5, etc. Preferably, the mass ratio of the calcined product to the carbon source additive is 10:5, so that the technical solution of the present invention can achieve better results.

[0025] Furthermore, the heating rate of the second calcination is 1~3℃ / min, the calcination temperature is 700~1100℃, and the holding time is 0.5~3 h.

[0026] Furthermore, the air flow rate is 1~3 m³ / h. 3 / h.

[0027] A second objective of this invention is to provide nano-alumina prepared by the aforementioned preparation method.

[0028] Furthermore, the nano-alumina has an α-phase content of ≥96%, a purity of ≥99.995%, a spherical morphology, an average particle size of 50~180 nm, a particle size distribution range of ≤0.8, and a specific surface area of ​​10~40 m². 2 / g.

[0029] Furthermore, the quasi-spherical shape includes one or more of the following: sphere, ellipsoid, stretched sphere, flattened sphere, spherical shape with undulating surface, and quasi-spherical polyhedron.

[0030] A third objective of this invention is to provide applications of the aforementioned nano-alumina in fields such as semiconductors, new energy and electronic packaging, and ceramic matrix composites.

[0031] The beneficial effects of this invention are:

[0032] (1) The raw material alumina in this invention undergoes at least two hydrothermal treatments. The first hydrothermal reaction removes most of the soluble ionic impurities and "squeezes out" the impurities from the main aluminum structure through a preliminary phase change, thus achieving preliminary purification. The subsequent hydrothermal reaction achieves "metabolism" inside the solid phase through deep recrystallization and Ostwald ripening, deeply removing the impurities that remain, are encapsulated, or are co-precipitated in the first step, and finally obtaining alumina with more complete crystals and purer chemical composition.

[0033] (2) The alumina product of this invention undergoes two calcinations. The first calcination causes the particles to form a worm-like sintered state, mainly composed of spherical single crystals. The sintered necks are then broken down into smaller particles and mixed with a carbon source additive before a second calcination. During the heating process in the absence of air, the carbon source additive is burned into carbon. After reaching the calcination temperature, air is introduced and the temperature is maintained, causing the carbon source to undergo a combustion reaction and instantly releasing a large amount of heat. This heat causes localized melting in defective areas on the particle surface. The molten alumina gradually grows and fuses through mass migration and surface energy minimization mechanisms, ultimately forming a spherical or more compact particle structure. This process not only achieves particle spherization but also effectively repairs structural defects on the particle surface, reducing the phenomenon of sintering and adhesion between nanoparticles, forming a worm-like shape, driven by surface energy, during the transformation of unstable phase nano-alumina to α-phase nano-alumina at temperatures above 1000℃.

[0034] (3) The method for preparing nano-alumina provided by this invention is simple and practical. Through multiple hydrothermal methods for "efficient impurity removal" and two calcinations for "shaping", the entire production process does not require harmful chemical reagents to treat impurities, nor does it require the addition of harmful additives such as mineralizers to control the morphology of alumina. The process is simple, green and environmentally friendly, and beneficial to industrial production. Attached Figure Description

[0035] Figure 1 The image shows an SEM image of the alumina product from Example 1, with the inset in the upper left corner being a particle size distribution diagram.

[0036] Figure 2 The image shows an SEM image of the alumina product from Example 2. The inset in the upper left corner of the image is a particle size distribution diagram.

[0037] Figure 3 The image shows an SEM image of the alumina product in Comparative Example 3. The inset in the upper left corner of the image is a particle size distribution diagram.

[0038] Figure 4 The image shows an SEM image of the alumina product from Example 4. The inset in the upper left corner of the image is a particle size distribution diagram.

[0039] Figure 5 The image shows an SEM image of the alumina product from Example 5, with the inset in the upper left corner being a particle size distribution diagram.

[0040] Figure 6 The image shows an SEM image of the alumina product from Example 6, with the inset in the upper left corner being a particle size distribution diagram.

[0041] Figure 7 The image shows an SEM image of the alumina product from Example 7, with the inset in the upper left corner being a particle size distribution diagram.

[0042] Figure 8 The image shows an SEM image of the alumina product in Comparative Example 1. The inset in the upper left corner of the image is a particle size distribution diagram.

[0043] Figure 9 The image shows an SEM image of the alumina product in Comparative Example 2. The inset in the upper left corner of the image is a particle size distribution diagram.

[0044] Figure 10 The image shows an SEM image of the alumina product in Comparative Example 3. The inset in the upper left corner of the image is a particle size distribution diagram.

[0045] Figure 11 The image shows an SEM image of the alumina product in Comparative Example 4. The inset in the upper left corner of the image is a particle size distribution diagram.

[0046] Figure 12 The image shows an SEM image of the alumina product in Comparative Example 5. The inset in the upper left corner of the image is a particle size distribution diagram.

[0047] Figure 13 The image shows an SEM image of the alumina product in Comparative Example 5. The inset in the upper left corner of the image is a particle size distribution diagram.

[0048] Figure 14 The XRD patterns of the alumina products from Examples 1-7 and Comparative Examples 1-5 are shown.

[0049] Figure 15 The image shows the XRD pattern of alumina, the product of Comparative Example 6. Detailed Implementation

[0050] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further described below with reference to specific embodiments and illustrations.

[0051] The alumina used in the following examples and comparative examples was purchased from China Aluminum, with a γ-phase content of 96% and a particle size of 80 μm, which was ground to a particle size of 8 μm; the starch was purchased from COFCO Biotechnology, specifically corn starch.

[0052] Example 1

[0053] (1) Alumina was mixed with deionized water to form a slurry with a solid content of 30%. The slurry was placed in a hydrothermal reactor and heated to 120°C for 30 h. After the reaction, the product was washed with deionized water until EC < 50 μS / cm to obtain the first hydrothermal reaction product. The first hydrothermal reaction product was then mixed with deionized water to form a slurry with a solid content of 40%. The slurry was placed in a hydrothermal reactor and heated to 190°C for 24 h. After the reaction, the product was washed with deionized water until EC < 50 μS / cm, dried, and the reaction product was obtained. The product was then dispersed to D using an air jet mill. 50 It is 0.2 μm.

[0054] (2) The reaction product prepared in step (1) was placed in a muffle furnace and heated to 1100℃ in an air atmosphere for calcination for 3 h. After calcination, the calcined product was dispersed into D using an air jet mill. 50 It is 0.3 μm.

[0055] (3) The calcined product prepared in step (2) is mixed with starch at a mass ratio of 10:3 and then placed in a tube furnace. Under vacuum conditions, the temperature is increased to 900°C at a heating rate of 1°C / min, and then increased at a rate of 2 m 3 Air was continuously introduced at a ventilation rate of / h and calcined at 900℃ for 1 h to obtain nano-alumina.

[0056] Example 2

[0057] (1) Same as Example 1.

[0058] (2) The reaction product prepared in step (1) was placed in a muffle furnace and heated to 1200℃ in an air atmosphere for calcination for 1 h. After calcination, the calcined product was dispersed into D using an air jet mill. 50 It is 0.25 μm.

[0059] (3) The calcined product prepared in step (2) is mixed with starch at a mass ratio of 10:3.5 and then placed in a tube furnace. Under vacuum conditions, the temperature is increased to 950°C at a heating rate of 1°C / min, and then decreased at a rate of 2.5 m. 3 Air was continuously introduced at a ventilation rate of / h and calcined at 950℃ for 1.5 h to obtain nano-alumina.

[0060] Example 3

[0061] (1) Same as Example 1.

[0062] (2) The reaction product prepared in step (1) was placed in a muffle furnace and heated to 1100℃ in an air atmosphere for calcination for 1 h. After calcination, the calcined product was dispersed into D using an air jet mill. 50 It is 0.4 μm.

[0063] (3) The calcined product prepared in step (2) is mixed with starch at a mass ratio of 10:5 and then placed in a tube furnace. Under vacuum conditions, the temperature is increased to 950°C at a heating rate of 3°C / min, and then further increased at a heating rate of 3 m / min. 3 Air was continuously introduced at a ventilation rate of / h and calcined at 950℃ for 1.5 h to obtain nano-alumina.

[0064] Example 4

[0065] (1) Same as Example 1.

[0066] (2) The reaction product prepared in step (1) was placed in a muffle furnace and heated to 1100℃ in an air atmosphere for calcination for 1 h. After calcination, the calcined product was dispersed into D using an air jet mill. 50 It is 0.1 μm.

[0067] (3) The calcined product prepared in step (2) is mixed with starch at a mass ratio of 10:1 and placed in a tube furnace. Under vacuum conditions, the temperature is increased to 1050℃ at a heating rate of 1℃ / min, and then increased at a rate of 2 m 3 Air was continuously introduced at a ventilation rate of / h and calcined at 1050℃ for 1 h to obtain nano-alumina.

[0068] Example 5

[0069] (1) Alumina was mixed with deionized water to form a slurry with a solid content of 30%. The slurry was placed in a hydrothermal reactor and heated to 120°C for 30 h. After the reaction, the product was washed with deionized water until EC < 50 μS / cm to obtain the first hydrothermal reaction product. The first hydrothermal reaction product was then mixed with deionized water to form a slurry with a solid content of 40%. The slurry was placed in a hydrothermal reactor and heated to 190°C for 24 h. After the reaction, the product was washed with deionized water until EC < 50 μS / cm to obtain the second hydrothermal reaction product. The second hydrothermal reaction product was then mixed with deionized water to form a slurry with a solid content of 40%. The slurry was placed in a hydrothermal reactor and heated to 190°C for 24 h. After the reaction, the product was washed with deionized water until EC < 50 μS / cm, dried, and the resulting reaction product was dispersed into D using an air jet mill. 50 It is 0.2 μm.

[0070] (2) Same as Example 1.

[0071] (3) Same as Example 1.

[0072] Example 6

[0073] (1) Same as Example 1.

[0074] (2) Same as Example 1.

[0075] (3) The calcined product prepared in step (2) is mixed with glucose at a mass ratio of 10:5 and placed in a tube furnace. Under vacuum conditions, the temperature is increased to 900°C at a heating rate of 1°C / min, and then increased at a rate of 2 m 3 Air was continuously introduced at a ventilation rate of / h and calcined at 900℃ for 1 h to obtain nano-alumina.

[0076] Example 7

[0077] (1) Same as Example 1.

[0078] (2) Same as Example 1.

[0079] (3) The calcined product prepared in step (2) is mixed with carbon black (industrial grade) at a mass ratio of 10:3 and then placed in a tube furnace. Under vacuum conditions, the temperature is increased to 900℃ at a heating rate of 1℃ / min, and then further increased at a rate of 2 m 3 Air was continuously introduced at a ventilation rate of / h and calcined at 900℃ for 1 h to obtain nano-alumina.

[0080] Comparative Example 1

[0081] (1) Alumina and deionized water were mixed to form a slurry with a solid content of 30%. The slurry was placed in a hydrothermal reactor and heated to 120°C for 30 h. After the reaction, the product was washed with deionized water until EC < 50 μS / cm, dried, and the resulting reaction product was dispersed into D using an air jet mill. 50 It is 0.2 μm.

[0082] (2) Same as Example 1.

[0083] (3) Same as Example 1.

[0084] Comparative Example 2

[0085] (1) Alumina and deionized water were mixed to form a slurry with a solid content of 40%. The slurry was placed in a hydrothermal reactor and heated to 190°C for 24 h. After the reaction, the product was washed with deionized water until EC < 50 μS / cm, dried, and the resulting reaction product was dispersed into D using an air jet mill. 50 It is 0.2 μm.

[0086] (2) Same as Example 1.

[0087] (3) Same as Example 1.

[0088] Comparative Example 3

[0089] (1) Same as Example 1.

[0090] (2) Place the reaction product prepared in step (1) in a muffle furnace and heat it to 1100℃ in an air atmosphere for calcination for 3 h.

[0091] (3) The calcined product prepared in step (2) is mixed with starch at a mass ratio of 10:3 and then placed in a tube furnace. Under vacuum conditions, the temperature is increased to 900°C at a heating rate of 1°C / min, and then increased at a rate of 2 m 3 Air was continuously introduced at a ventilation rate of / h and calcined at 900℃ for 1 h to obtain nano-alumina.

[0092] Comparative Example 4

[0093] (1) Same as Example 1.

[0094] (2) The reaction product prepared in step (1) was placed in a muffle furnace and heated to 1100℃ in an air atmosphere for calcination for 3 h. After calcination, the calcined product was dispersed into D using an air jet mill. 50 It is 0.3 μm.

[0095] (3) The calcined product prepared in step (2) is placed in a tube furnace and heated to 900°C at a heating rate of 1°C / min under vacuum conditions, and then heated at a rate of 2 m 3 Air was continuously introduced at a ventilation rate of / h and calcined at 900℃ for 1 h to obtain nano-alumina.

[0096] Comparative Example 5

[0097] (1) Same as Example 1.

[0098] (2) Same as Example 1.

[0099] (3) The calcined product prepared in step (2) is mixed with starch at a mass ratio of 10:6 and then placed in a tube furnace. Under vacuum conditions, the temperature is increased to 900°C at a heating rate of 1°C / min, and then further increased at a rate of 2 m 3 Air was continuously introduced at a ventilation rate of / h and calcined at 900℃ for 1 h to obtain nano-alumina.

[0100] Comparative Example 6

[0101] (1) Same as Example 1.

[0102] (2) The reaction product prepared in step (1) is mixed with starch at a mass ratio of 10:3 and then placed in a tube furnace. Under vacuum conditions, the temperature is increased to 900°C at a heating rate of 1°C / min, and then increased at a rate of 2 m 3 Air was continuously introduced at a ventilation rate of / h and calcined at 900℃ for 1 h to obtain nano-alumina.

[0103] The performance of the nano-alumina prepared in Examples 1-7 and Comparative Examples 1-6 was tested, and the results are shown in Table 1.

[0104] Morphology was determined using scanning electron microscopy (SEM), see below. Figures 1-12 ;

[0105] The α-phase content was determined using X-ray diffraction (XRD), see [reference needed]. Figures 13-14 ;

[0106] Purity was determined using inductively coupled plasma optical emission spectrometry (ICP-OES).

[0107] Specific surface area was determined using the nitrogen adsorption-desorption (BET) method.

[0108] Particle size was measured using a laser particle size analyzer, and the particle size distribution span was calculated using the following formula.

[0109] Span = (D 90 - D 10 ) / D 50

[0110] Among them, D 10 D represents the particle size at which the cumulative volume distribution reaches 10%. 50 D represents the median particle size at which the cumulative volume distribution reaches 50%. 90 This indicates the particle size at which the cumulative volume distribution reaches 90%.

[0111] Table 1. Performance test results of nano-alumina prepared in Examples 1-7 and Comparative Examples 1-6

[0112] Example 1 96 spherical 99.9957 21.0 0.54 Example 2 96 spherical 99.9954 28.2 0.55 Example 3 97 spherical 99.9962 26.0 0.55 Example 4 96 spherical 99.9951 25.3 0.55 Example 5 98 spherical 99.9975 22.5 0.55 Example 6 96 spherical 99.9952 26.9 0.54 Example 7 97 spherical 99.9981 26.7 0.57 Comparative Example 1 95 spherical + irregular 98.2112 12.3 0.57 Comparative Example 2 96 Irregular large particles 98.9235 5.3 3.19 Comparative Example 3 98 sintering 99.9901 9.7 3.00 Comparative Example 4 96 Irregular + fragmented particles 99.9953 34.2 0.55 Comparative Example 5 98 sintering 99.9926 8.9 3.29 Comparative Example 6 67 Porous + Sintering 99.9934 6.8 1.93

[0113] As shown in Table 1:

[0114] The nano-alumina prepared in Examples 1-7 is mainly composed of α-alumina, with an α-phase content of ≥96%, and the particles are spherical in shape, have high purity, a particle size of 50-180 nm, an extremely narrow particle size distribution, and a particle size distribution span of ≤0.8.

[0115] As can be seen from Example 1 and Comparative Example 1, two hydrothermal reactions can yield alumina with more complete crystals and purer chemical composition;

[0116] As can be seen from Example 1 and Comparative Example 2, a higher initial hydrothermal temperature directly leads to an increase in the initial crystallinity and particle size, which promotes the increase in the particle size of the finished product.

[0117] As can be seen from Example 1 and Comparative Example 3, the product from the first calcination, after being dispersed, approaches the nanoscale size. ,This provides the basis for the second calcination of the finished nanoparticles;

[0118] As can be seen from Example 1 and Comparative Example 4, the addition of carbon source additives allows the carbon source additives to be burned by air at the moment of the second low-temperature calcination. The released energy can melt the rough parts of the surface of the small particles and large particles, forming spherical alumina.

[0119] As can be seen from Example 1 and Comparative Example 5, an excess of carbon source additives will lead to a significant increase in instantaneous calcination temperature, which will further affect the morphology of the product due to sintering.

[0120] As can be seen from Example 1 and Comparative Example 6, adding a carbon source additive during calcination at low temperature cannot generate a high-purity α phase, while adding a carbon source additive during calcination at high temperature produces a large amount of worm-like products. Therefore, the present invention employs the aforementioned two-calcination method to obtain high-purity, near-spherical nano-alumina particles with an extremely narrow particle size distribution.

[0121] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing high-purity, high-α-phase nano-alumina, characterized in that, Includes the following steps: (1) Alumina is subjected to at least two hydrothermal reactions to obtain the reaction product; (2) The reaction product is calcined for the first time to obtain the calcined product; (3) The calcined product is mixed with carbon source additives and calcined a second time under vacuum or inert atmosphere. After reaching the calcination temperature, air is introduced and the temperature is maintained to obtain high-purity high α phase nano alumina.

2. The preparation method according to claim 1, characterized in that: The at least two hydrothermal reactions include a first hydrothermal reaction and at least one subsequent hydrothermal reaction; preferably, the reaction temperature of the subsequent hydrothermal reaction is higher than that of the first hydrothermal reaction.

3. The preparation method according to claim 1, characterized in that: The first hydrothermal reaction has a slurry solid content of 10-50%, a reaction temperature of 100-130℃, and a reaction time of 24-36 h; preferably, the subsequent hydrothermal reaction has a slurry solid content of 30-60%, a reaction temperature of 180-230℃, and a reaction time of 10-36 h.

4. The preparation method according to claim 1, characterized in that: The first calcination is carried out in an air or oxygen atmosphere; preferably, the calcination temperature of the first calcination is 1100~1300℃, and the holding time is 1~5 h; preferably, after the first calcination, the calcined product is dispersed to an average particle size of 0.1~0.3 μm.

5. The preparation method according to claim 1, characterized in that: The carbon source additive is an organic carbon source and / or a carbon material; preferably, the organic carbon source is one or more of sugars, polyols, organic acids, and oxygen-containing polymers; preferably, the organic carbon source is one or more of glucose, fructose, sucrose, maltose, lactose, starch, cellulose, glycerol, and lignin; preferably, the carbon material is one or more of graphite, carbon black, graphene, carbon nanotubes, amorphous carbon, fullerene, and diamond.

6. The preparation method according to claim 1, characterized in that: The second calcination involves a heating rate of 1-3°C / min, a calcination temperature of 700-1100°C, and a holding time of 0.5-3 h; preferably, the air flow rate is 1-3 m³ / min. 3 / h.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the calcined product to the carbon source additive is 10:(1~5); preferably, the mass ratio of the calcined product to the carbon source additive is 10:

5.

8. High-purity high-α phase nano-alumina prepared by the preparation method according to any one of claims 1 to 7.

9. The high-purity, high-α-phase nano-alumina according to claim 8, characterized in that: The nano-alumina has an α-phase content of ≥96%, a purity of ≥99.995%, a spherical morphology, an average particle size of 50~180 nm, a particle size distribution range of ≤0.8, and a specific surface area of ​​10~40 m². 2 / g; Preferably, the quasi-spherical shape includes one or more of the following: sphere, ellipsoid, stretched sphere, flattened sphere, spherical with undulating surface, and quasi-spherical polyhedron.

10. The application of the high-purity, high-α phase nano-alumina as described in claim 8 or 9 in semiconductors, new energy and electronic packaging, and ceramic matrix composites.

Citation Information

Patent Citations

  • Preparation method of electronic-grade spheroidic alpha-Al2O3 powder

    CN115818690A

  • Vacancy isolation preparation method of monodisperse nano alpha alumina

    CN119911947A